P294 Alternative diagnoses in patients with functional diarrhoea and treatment outcomes. (19th June 2022) - Poon, Dennis; Major, Giles; Andreyev, Jervoise
Abstract : Introduction: Conditions such as bile acid diarrhoea (BAD), small intestinal bacterial overgrowth (SIBO) and pancreatic exocrine insufficiency (PEI) may go undetected where individuals are given a diagnosis of irritable bowel syndrome (IBS). We aimed to examine how frequently such conditions would be identified in a young patient cohort referred to secondary care and meeting accepted criteria for diarrhoea-predominant IBS (IBS-D) and functional diarrhoea (FD), and the impact of relevant treatment on symptoms. Methods: Between April and November 2019, all patients referred to Lincoln County Hospital meeting the Rome IV criteria for IBS-D and FD were offered comprehensive investigations including stool tests for faecal elastase-1 and calprotectin, 75 selenium homocholic acid taurine scan (SeHCAT), hydrogen methane breath tests (HMBT), and endoscopies with duodenal and colonic biopsies. GI conditions identified following these tests were treated and response was assessed using a modified gastrointestinal symptom rating scale (GSRS) at presentation and after treatment. Quality of life was also captured using a 10-point visual analogue scale at both endpoints. Paired scores comparisons were undertaken using Wilcoxon non-parametric tests to check for significant changes in symptom score and quality of life before and after treatment. Results: 66 patients (15 males and 51 females) with a median age of 34 (range 18-50) were included in this study. 44 met the Rome IV criteria for IBS-D and 22 for FD. 64 patients had stool tests; 56 had a SeHCAT, 57 had a lactulose HMBT, 38 had a gastroscopy and 43 had a lower GI endoscopy. Two patients (3%) were found to have colonic malignancy; 21 (37.5%) had BAD; one (1.5%) had PEI; two (3%) had villous atrophy on their duodenal biopsies but a negative coeliac serology; 31 (54.4%) met the diagnostic criteria for SIBO. 39 patients (59.1%) had more than one alternative GI diagnoses. Significant improvement in symptoms and quality of life were noted following treatment of newly diagnosed conditions. These changes were most noticeable in those with BAD and SIBO. The baseline and post treatment median GSRS scores in the BAD cohort were 35 (range 10-48) and 17 (range 3-9), p= 0.0005, with quality of life improved from a median of 6 (range 1-10) to 8 (range 3-10), p= 0.0002. The GSRS scores of those with SIBO improved from a baseline median of 30 (range 10-50) to 16 (range 1-47), p= 0.0002; the quality of life improved from 5 (range 0-8) to 7 (range 2-10), p= 0.004. Conclusions: A number of treatable GI disorders were detected in our patient cohort. Treating these conditions appropriately led to at least short-term significant improvement in patient reported symptoms and quality of life.